Moving to a Flexible Exchange Rate : How, When, and How Fast? - Duttagupta, Rupa (Economic Issues; Economic Issues ;, 2007)
A growing number of countries are adopting flexible exchange rate regimes because flexibility offers more protection against external shocks and greater monetary independence. Other countries have made the transition under disorderly conditions, with the sharp depreciation of their currency during a crisis. Regardless of the reason for adopting a flexible exchange rate, a successful transition depends on the effective management of a number of institutional and operational issues. The authors of this Economic Issue describe the necessary ingredients for moving to a flexible regime, as well as the optimal pace and sequencing under different conditions.